Moderasi Beragama untuk Generasi Milenial Pancasila - Imam Wahyuddin; Agus Hilmawan Utomo; Fitri Alfaris; Fajar Cahyono; Ashari Ashari (LPPM IAIN Sorong, 2022)
Religious harmony and tolerance in the village of “Pancasila” Balun, Turi, Lamongan, East Java, is a lesson for the practice of religious moderation which needs to be learned and used as an example. All of studies that already exist, the principle of harmony and tolerance in Balun village is the result of nonformal education construction, even though talking about character building could not be divided from the role of formal educational institutions. This research is trying to complement the formal religious education institution which in this case is Madrasah Ibtidaiah (MI) Tarbiyatus Sibyan in establishing and strengthening religious moderation in the village of “Pancasila” Balun. This is a qualitative research with a formal object of religious moderation and the object of MI Tarbiyatus Sibyan. Data collection was done by literature study, interviews, and FGD with teachers and students of MI Tarbiyatus Sibyan. This research shows: (1) MI Tarbiyatus Sibyan was considering religious moderation as part of the local wisdom of the village that must be preserved and maintained; (2). MI Tarbiyatus Sibyan instilling insight into religious moderation in the learning process through the internal class activities and external by visiting the Jawi Wetan Balun Christian Church; and (3). MI Tarbiyatus Sibyan students was playing an important role in supporting socio-religious activities in Balun village. In summary, this study explains the contribution of formal education in which local wisdom can strengthen students' religious moderation insight. Therefore, it is necessary to develop formal educational institutions which defend local wisdom as part of the emphasis on the educational process in madrasas or schools.